Atomic-level design of CoOH+-hydroxyapatite@C catalysts for superfast degradation of organics via peroxymonosulfate activation - Song, F.; Zhang, H.; Wang, Shaobin; Liu, L.; Tan, X.; Liu, Shaomin (The Royal Society of Chemistry, 2018)
We report a strategy for simultaneous cobalt removal and organic waste decomposition by using mesoporous hydroxyapatite nanoparticles wrapped in uniform carbon layers (HA@C). The in situ formation of CoOH+-HA@C due to ion exchange greatly improved the degradation efficiency by at least one order of magnitude compared to free Co2+.